Rational Speculation, Financial Crises, and Optimal Policy Responses - Surti, Jay (IMF Working Papers; Working Paper ;, 2004)
This paper develops a theory of the onset of financial crises by solving for the optimal trading strategies of speculators in financial markets, in a model where each speculator tries to coordinate her trades with the market's by observing the decisions of other speculators, while simultaneously trying to preempt the market. The interaction and resolution of these two conflicting incentives are analyzed under alternate central bank policy regimes. Our model explains how imperfect information structures prevent traders from exploiting profitable opportunities and suggests how large traders help alleviate this problem by undertaking risky arbitrage early in the investment process, in return for higher profits, if successful. The central bank's defense strategy is a parameter of this model. We compare the likelihood of a crisis under alternate defense strategies and show that credible monetary authorities can provide a better defense of exchange rate regimes against adverse shocks by not disclosing their commitment value to the market.